Reframing Language Policy and Multilingual Education in the Indonesian Context - Sevtianto, Bagus (Pemuda Peduli Publikasi Insan Ilmiah, 2025)
Purpose: This study explores the reframing of language policies and multilingual education in Indonesia, focusing on how language proficiency and multilingual education programs affect students' academic performance. The aim was to identify the challenges and opportunities of integrating local languages, Bahasa Indonesia, and global languages like English into the educational system. Subjects and Methods: Using a mixed-methods approach, the study combined quantitative surveys and qualitative interviews to gather data from students, teachers, school administrators, and policymakers across Indonesia. Results: The findings revealed that proficiency in Bahasa Indonesia was positively correlated with academic success, yet bilingualism, particularly in local languages, also enhanced cognitive flexibility and improved academic outcomes. The study highlighted significant regional disparities, with urban schools demonstrating better implementation of multilingual education programs compared to rural areas. Teachers and students expressed positive views on multilingual education, but the implementation of policies was often inconsistent and lacked clear guidance. The study contributes to the body of knowledge on multilingual education by providing empirical data on the impact of language policies in Indonesia. Conclusions: The findings suggest that more inclusive and flexible language policies are needed to address the diverse linguistic needs of students, particularly in rural areas. Further research is needed to evaluate the long-term effects of multilingual education on students' socio-economic outcomes and its role in fostering national unity.